Analysis of Mixed Economic System in Islamic Perspective - Riyardi, Agung; Santosa, Purbayu Budi (Semarang State University, 2015)
This study try to analyze a mixed economic system, based on Islamic rules. It is regarded as an ideal system in economic because goverment economic plays role in the system. Nowdays, many concepts of mixed economic system come up but it can not be said as the ideal ones as economic actorsâ greediness interferes the systems. The method for analizing data is placing the goverment and private sectors appropriately at a curve ofÂ procuction possibility of private-public goods. There are some findings. The first result shows that the goverment does not need to condunct market operation and price interference with the assumption of the poor can meet their basic needs. Then, Islam views that mixed economic system is the ideal one if goverment and private sector play roles in the system. The role of goverment is to provide goods for public and controll private sectors. Further, the private sectors provide goods for the needs of private. Finally, the finding also shows that there is greediness, appears at the goverment and private system.